A Tour of Dependable Computing Research in Latin America. - DUARTE JR., ELIAS P.; MACÊDO, RAIMUNDO J. A.; MARTINS, ELIANE; RAJSBAUM, SERGIO (Communications of the ACM, 2020)
The article examines computing research in Latin America, particularly focusing upon dependable computing in Latin America (LATAM). It discusses the development of fault prevention and fault tolerance and, as such, the design of fault-tolerant architectures for computer security, the challenges of widely distributed, mobile systems, and results from research conducted at the National Institute for Space Research (INPE) in Brazil.